Hypoxia-inducible factor-1α induces CX3CR1 expression and promotes the epithelial to mesenchymal transition (EMT) in ovarian cancer cells - Santosh Kumar Singh; Manoj Kumar Mishra; Rajesh Singh (BMC, 2019)
Abstract Background Chemokines are involved in the homing of various cancer cells, including those of ovarian cancer (OvCa), to distant organs. They may also promote or inhibit cancer progression and metastasis. Hypoxia, a common phenomenon in malignant tumors, promotes cell proliferation regulated by HIF-1α. Hypoxia-induced genes are involved in metastasis-associated functions and in the epithelial-to-mesenchymal transition (EMT). Results Tissue microarrays of human OvCa showed elevated expression of CX3CR1 and HIF-1α compared to normal cells, and their levels were higher in adenocarcinoma stages II and III. To substantiate these observations, we performed studies using OvCa cells. Following exposure to hypoxia, OVCAR-3, SW 626, and TOV-112D cells showed high expression of CX3CR1, a transmembrane protein involved in the adhesion and migration of leukocytes, causing an increased chemotactic response to CX3CL1, the ligand for CX3CR1. As determined by flow cytometry, immunofluorescence, RT-PCR, and western blots, there were higher expressions of CX3CR1 and HIF-1α in OvCa cell lines exposed to hypoxia. Further, OvCa cells expressing CX3CR1 were sensitive to the CX3CL1 ligand. Chemotaxis based on chemokine receptors was influential in elevating the expression of EMT markers and matrix metalloproteinases, which are involved in the progression and metastasis of cancer cells. Conclusions In OvCa cells, CX3CR1 was upregulated in a process involving hypoxia-mediated regulation of HIF-1α. The elevated levels of CX3CR1, which were sensitive to CX3CL1, increased EMT markers that led to the progression and metastasis of OvCa. Thus, CX3CR1 and HIF-1α are suitable targets for treatment of OvCa.